2011
DOI: 10.1007/s12639-011-0030-y
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal coccidian parasitic infections in rural community in and around Loni, Maharashtra

Abstract: Fecal samples examination of 310 individuals with variable gastro-intestinal (GI) disturbances but negative for intestinal parasites or bacterial pathogens, revealed 97 persons positive for infection with coccidian parasites employing modified Ziehl-Neelsen (ZN) staining and Sheather's sucrose floatation technique. Cryptosporidium oocysts alone were detected in 64 (64/97; 66%) cases whereas Cyclospora oocysts along with Cryptosporidium were present in other 30 cases (31%); remaining three cases yielded only Cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Moreover, the microscopic method for identification of intestinal coccidian include finding the characteristic spherical oocysts in a faecal smear or formol‐ether concentrated faecal samples using acid‐fast stain or auramine‐rhodamine stain . The oocysts of both Cryptosporidium species , Cyclospora and Isospora, are detected in faeces by employing modified Ziehl–Neelsen (ZN) staining and Sheather's sucrose floatation technique . Additionally, weber's chromotrope‐based stain has been used for diagnosing microsporidial infections caused by Enterocytozoon bieneusi in faeces by light microscopy examination .…”
Section: Traditional Approaches For Detection Of Luminal Protozoa Andmentioning
confidence: 99%
“…Moreover, the microscopic method for identification of intestinal coccidian include finding the characteristic spherical oocysts in a faecal smear or formol‐ether concentrated faecal samples using acid‐fast stain or auramine‐rhodamine stain . The oocysts of both Cryptosporidium species , Cyclospora and Isospora, are detected in faeces by employing modified Ziehl–Neelsen (ZN) staining and Sheather's sucrose floatation technique . Additionally, weber's chromotrope‐based stain has been used for diagnosing microsporidial infections caused by Enterocytozoon bieneusi in faeces by light microscopy examination .…”
Section: Traditional Approaches For Detection Of Luminal Protozoa Andmentioning
confidence: 99%
“…Few studies have reported frequency of Cryptosporidium spp to be 21% in Chennai and 66% in Maharashtra. 15,16 Prevalence in north India ranges from 36% to 50% in adult diarrhea cases. 10,17 A review of 78 reports has shown that Cryptosporidium spp prevalence varies in developed and developing nations with seropositivity has high as 90% in Brazil and 50% in China to 22% in high income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Las infecciones por coccidios intestinales se encuentran ampliamente distribuidas en el mundo, detectándose tasas de prevalencias muy variadas: China (12%) 8 , Nepal (5,6%-14,1%) 9 , Polonia (5,4%) 10 , India (1,13-31,29%) 11,12 , Arabia Saudita (19,23%) 13 , Nigeria (2,2-32,2) 14 , Costa de Marfil (3,9-7,7%) 15 , Etiopía (7,9-20,8%) 16 , Libia (0.9-13%) 17 . Para países de Latinoamérica, se han encontrado cifras de prevalencia variables similares, incluyendo Guatemala (7,14-13,7%) 18 , México (9,,4%) 19,20 , Argentina (1,3%) 21 , Perú (4->40%) 22 .…”
Section: Introductionunclassified